A composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate, preparation method and application thereof
Through the combination of fermented silk protein peptide and hydrolyzed sodium hyaluronate, the problems of dry and frizzy hair and easy breakage are solved, and better combing and water retention are achieved, which significantly improves the flexibility and toughness of hair.
Patent Information
- Application Number
- CN202411857779.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to effectively solve problems such as dry and frizzy hair, reduced flexibility, damaged hair quality, and easy breakage, especially after frequent washing, perming and styling.
A composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate is provided. By combining fermented silk protein peptide and hydrolyzed sodium hyaluronate, its combing performance and water retention properties are optimized and hair quality is improved.
The composition significantly improves dry and frizzy hair, makes it smoother and brighter, enhances the toughness and anti-pollution ability of the hair, and reduces the phenomenon of hair breakage.
Smart Images

Figure CN119770377A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of daily chemical products, and specifically relates to a composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate, a preparation method and application thereof. Background Art
[0002] Silk fibroin peptide (SFP) contains 18 kinds of amino acids, including almost all the amino acids needed by the human body, especially the nutritional amino acids (glycine, alanine, serine, tyrosine) that are very necessary for human skin and hair. Its content accounts for more than 80% of the total amino acids, which is unattainable by other hydrolyzed proteins. Silk protein is a natural high-molecular fiber protein extracted from silk, accounting for about 70% to 80% of silk. Silk protein can be hydrolyzed into small-molecule silk protein peptides. The molecular weight of silk protein peptides is closely related to the performance of hair care effects. Small-molecule silk protein peptides have strong penetration ability and can achieve better hair care effects.
[0003] Sodium hyaluronate belongs to the glycosaminoglycan compound and is a member of the polysaccharide family. Chemically, hyaluronic acid is a hydrophilic macromolecule with -COOH and -OH functional groups. It has high solubility in water and can form a high-viscosity solution, which makes it show unique viscoelasticity. Sodium hyaluronate can form intramolecular hydrogen bonds, which can capture water in its structure and form a gel. The amount of water captured is about 1000 times its weight. Most products with sodium hyaluronate as the main ingredient, such as body lotion, face cream, lipstick, essence, etc., are targeted at the skin, while there are very few products that act on the hair. On this basis, there are even fewer products that claim to toughen or resist frizz. Sodium hyaluronate has both water absorption properties and multiple carboxyl groups and has a strong ability to form hydrogen bonds, which proves that it may have a strong potential for repairing hair.
[0004] Nowadays, people have an increasing demand for hair care, and the frequency of hair washing, perming, dyeing and styling is high. In addition, environmental stress can easily cause hair damage. These factors often lead to dry and frizzy hair, decreased smoothness, damaged hair, and easy breakage. Therefore, the development of active ingredients with strong hair care effects has become a research hotspot. Summary of the invention
[0005] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0006] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0007] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate.
[0008] In order to solve the above technical problems, the present invention provides the following technical solution: a composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate, comprising:
[0009] 1kDa fermented silk protein peptide, 1-10kDa sodium hyaluronate, 10-50kDa sodium hyaluronate and deionized water;
[0010] Among them, based on the mass percentage of each raw material, the molecular weight of 1kDa fermented silk protein peptide is 0.5-20%, the molecular weight of 1-10kDa sodium hyaluronate is 0.1-10%, the 10-50kDa sodium hyaluronate is 0.1-10%, and the rest is made up to 100% with deionized water.
[0011] As a preferred embodiment of the composition of the present invention, the molecular weight of the sodium hyaluronate with a molecular weight of 1-10 kDa is 7 kDa.
[0012] As a preferred embodiment of the composition of the present invention, the molecular weight of the sodium hyaluronate with a molecular weight of 10-50 kDa is 11 kDa.
[0013] As a preferred embodiment of the composition of the present invention, the content of the fermented silk protein peptide with a molecular weight of 1 kDa is 1%, the content of the sodium hyaluronate with a molecular weight of 7 kDa is 0.4%, the content of the sodium hyaluronate with a molecular weight of 11 kDa is 0.6%, and the remaining deionized water is supplemented to 100%.
[0014] As a preferred embodiment of the composition of the present invention, the method for preparing the fermented silk protein peptide with a molecular weight of 1 kDa comprises:
[0015] Silk protein powder was dissolved in deionized water, pasteurized, and cooled to obtain solution A;
[0016] Dissolve anhydrous glucose in deionized water, sterilize by high pressure, and cool to obtain solution B;
[0017] Mixing solution A and solution B evenly under sterile conditions to prepare a fermentation medium;
[0018] The plant lactobacillus was cultured in MRS medium until OD600nm=7-8, then inoculated into the fermentation medium at a volume fraction of 2%-5%, and cultured in a 37°C constant temperature incubator for 24-48 hours, and the fermentation was terminated when the residual sugar reached 0;
[0019] After the fermentation is completed, the fermentation liquid is filtered through a 0.2 μm microfiltration membrane, and the filtrate is a fermented silk protein peptide solution with a molecular weight of 1 kDa.
[0020] As a preferred embodiment of the composition of the present invention, the plant lactobacillus is plant lactobacillus (Lactobacilusplantarum) ZW, which is deposited in the China Center for Type Culture Collection with a deposit number of CCTCC NO: M20232390 and a deposit date of November 29, 2023. The strains involved in the above technical content have related patent application numbers of 202311809096.1 and 202311808800.1.
[0021] Another object of the present invention is to overcome the deficiencies in the prior art and provide a method for preparing a composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate, comprising uniformly mixing fermented silk protein peptide with a molecular weight of 1 kDa, sodium hyaluronate with a molecular weight of 1 to 10 kDa, sodium hyaluronate with a molecular weight of 10 to 50 kDa and deionized water to obtain the composition.
[0022] Another object of the present invention is to overcome the deficiencies in the prior art and provide a composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate for use in preparing hair care products.
[0023] As a preferred solution of the application of the present invention, it includes:
[0024] Prepare raw materials: 400Da hydrolyzed collagen, 10kDa hydrolyzed keratin, and the composition;
[0025] Mixing evenly: mixing 400Da hydrolyzed collagen, 10kDa hydrolyzed keratin and the composition evenly to prepare the hair care product.
[0026] Beneficial effects of the present invention:
[0027] (1) The present invention provides a new low-molecular hair care composition with multiple hair care effects, which utilizes low-molecular active ingredient fermented silk protein peptides to supplement the nutrients missing in damaged hair and the water absorption, moisture retention and film-forming properties of sodium hyaluronate to provide a new raw material product for the hair care field; the present invention uses the multi-enzyme system of microorganisms to hydrolyze silk protein, thereby obtaining small-molecule silk protein peptides with better penetration and permeability, and at the same time, lactobacillus fermentation products such as lactic acid, vitamins, antioxidants, etc., which have a positive effect on the health of hair and scalp; based on the water absorption and moisture retention properties of sodium hyaluronate, the present invention designs a combination formula of small-molecule silk protein peptides and small-molecule sodium hyaluronate, and obtains the optimal combination ratio by optimizing its combing performance and water retention performance. The combination of fermented silk protein peptides and hydrolyzed sodium hyaluronate greatly improves dry and frizzy hair, making it smoother and brighter.
[0028] (2) The present invention provides a product formula containing low-molecular hair care ingredients, which shows excellent efficacy in anti-pollution tests, permeability tests, surface performance tests, water retention tests, and tensile performance tests; the product formula is tested for its efficacy in strengthening hair and preventing frizz; the permeability of small molecule active ingredients is detected by fluorescent labeling and fluorescence microscopy, reflecting its efficacy in strengthening hair; in addition, in another dimension, the effects of combing work, friction coefficient, and surface dust deposition on hair are tested by a combing instrument, a single fiber friction coefficient meter, and SEM, verifying its efficacy in preventing hair breakage in other aspects; the multi-dimensional hair care efficacy of the product formula provided by the present invention enables it to be applied to various types of damaged hair. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0030] Figure 1 Dextran standard curve in Example 1 of the present invention
[0031] Figure 2 This is a diagram showing the results of the liquid phase detection of the fermented silk protein peptide in Example 2 of the present invention.
[0032] Figure 3 This is a graph showing the effects of different small molecule active ingredients on the combing performance of hair in Example 2 of the present invention.
[0033] Figure 4 This is a graph showing the effects of different small molecule composition treatments on the combing performance of hair bundles in Example 3 of the present invention.
[0034] Figure 5 This is a graph showing the effects of different small molecule composition treatments on the combing performance of hair in Example 4 of the present invention.
[0035] Figure 6 These are scanning electron microscope photos of the control group (a) and the product group (b) after being treated in the pollution simulation box in Example 6 of the present invention.
[0036] Figure 7 This is the cross section of the hair after being treated with the fluorescent labeling product sample under a fluorescence microscope in Example 7 of the present invention.
[0037] Figure 8 This is a graph showing the effect of product solution treatment on the dynamic friction coefficient of hair in Example 8 of the present invention.
[0038] Fig. 9 This is a graph showing the effect of product solution treatment on hair combing work in Example 8 of the present invention.
[0039] Fig.10 This is a graph showing the effect of product solution treatment on hair breaking strength in Example 10 of the present invention.
[0040] Fig.11 This is a graph showing the effect of product solution treatment on the tensile force in the yield zone of hair in Example 10 of the present invention. DETAILED DESCRIPTION
[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0042] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0043] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0044] The implementation method of this experiment:
[0045] High performance liquid chromatography (HPLC) was used with the following detection conditions: the chromatographic column was a gel column Sec-300, the mobile phase was 0.1 M sodium nitrate, the flow rate was 0.3 mL / min, the column temperature was 25°C, a differential detector was used, and the injection volume was 20 μL.
[0046] Preparation of dextran standard solutions with different molecular weights: Dextran standard solutions with molecular weights (M) of 180, 2700, 5250, 9750, and 13050 were prepared at a concentration of 0.5 mg / mL.
[0047] The standard solution was tested according to the above conditions, and the standard curve was drawn with 1gM as the abscissa and the peak time as the ordinate to obtain the regression equation of the dextran standard curve.
[0048] Example 1
[0049] This embodiment provides a method for preparing silk protein peptides by fermenting silk protein with Lactobacillus plantarum, the main steps of which are:
[0050] (1) Seed medium MRS: peptone 10.0 g / L, beef extract 10.0 g / L, yeast extract 5.0 g / L, diammonium hydrogen citrate 2.0 g / L, glucose 20.0 g / L, Tween 80 1.0 mL / L, sodium acetate 5.0 g / L, dipotassium hydrogen phosphate 2.0 g / L, magnesium sulfate 0.58 g / L, manganese sulfate 0.25 g / L, pH 6.8. After the medium components are prepared, sterilize at 121°C for 20 min.
[0051] Fermentation medium: Solution A was 100 g of silk protein powder dissolved in 500 mL of deionized water, pasteurized at 65 °C for 30 min, and cooled to 37 °C;
[0052] Solution B was 20.0 g of anhydrous glucose dissolved in 500 mL of deionized water, autoclaved at 121 °C for 15 min, and then cooled to 37 °C;
[0053] Under sterile conditions, solution A and solution B are mixed evenly to obtain a fermentation medium.
[0054] (2) Fermentation process: Lactobacillus plantarum was cultured in MRS medium to OD600nm=7-8, and then inoculated into the fermentation medium at a volume fraction of 5%, and cultured in a constant temperature incubator at 37°C for 24 h. The residual glucose and lactic acid were detected during the fermentation process, and the fermentation was terminated based on the complete consumption of glucose.
[0055] Lactobacillus plantarum comes from the self-built strain bank of Jiangsu Ruiting Biotechnology Co., Ltd. The Lactobacillus plantarum is Lactobacillus plantarum (Lactobacilusplantarum) ZW, which is preserved in the China Center for Type Culture Collection with the preservation number CCTCCNO: M 20232390 and the preservation date is November 29, 2023; the strains involved in the above technical content have relevant patent application numbers 202311809096.1 and 202311808800.1.
[0056] (3) The fermentation liquid is filtered through a 0.2 μm microfiltration membrane, and the filtrate is the silk protein peptide fermentation product. The liquid phase detection results are shown in Figure 1 , 2 ,from Figure 2 It can be seen that a characteristic peak appeared at 9.720 min, and the average molecular weight of the silk protein peptide fermentation product was calculated to be 1 kDa.
[0057] Example 2
[0058] The combing performance and water retention performance of the 1 kDa fermented silk protein peptide obtained in Example 1, the commercially available 1 kDa silk protein peptide, 7 kDa sodium hyaluronate, 11 kDa sodium hyaluronate and 30 kDa sodium hyaluronate were tested. The commercially available 1 kDa silk protein peptide of the present invention was purchased from Qinhe Health Industry (Shaanxi) Co., Ltd.; 7 kDa sodium hyaluronate, 11 kDa sodium hyaluronate and 30 kDa sodium hyaluronate were all independently developed and produced by Jiangsu Ruiting Biotechnology Co., Ltd.
[0059] (1) Experimental sample preparation:
[0060] Control group: deionized water.
[0061] Sample 1: 1% aqueous solution of 1 kDa fermented silk protein peptide.
[0062] Sample 2: 1% aqueous solution of commercially available 1 kDa silk protein peptide.
[0063] Sample 3: 1% aqueous solution of 3 kDa sodium hyaluronate.
[0064] Sample 4: 1% 7 kDa sodium hyaluronate aqueous solution.
[0065] Sample 5: 1% aqueous solution of 11 kDa sodium hyaluronate.
[0066] Sample 6: 1% aqueous solution of 30 kDa sodium hyaluronate.
[0067] (2) Combing performance test:
[0068] The experiment was conducted at a temperature of (25±2)℃ and a RH of (50±5)%. A 40cm-long hair bundle that had been pre-treated and bleached twice was selected, and the hair bundle was fully moistened with warm water at 40℃. 5mL of a 10% SDS aqueous solution was taken with a dropper, and evenly applied to the front and back of the hair bundle and rubbed to foam. When rubbing, avoid folding the hair bundle in half or twisting it together to prevent the hair from tangling. Then rinse off the foam with warm water, repeat the above operation twice, and place it in a constant temperature and humidity environment to dry naturally.
[0069] The hair bundles were soaked in deionized water and six groups of experimental sample aqueous solutions for 4 hours. After soaking, all the hair bundles were rinsed with warm water. After rinsing with warm water, the hair was combed ten times with similar force by hand, and then dried under constant temperature and humidity conditions.
[0070] The dry combing work of each hair bundle was tested using a combing apparatus. Two hair pieces of the same specifications were used for each group and the test was repeated seven times.
[0071] The combing curve is obtained by data processing, and the combing work can be obtained by integrating the combing curve.
[0072] The results are as follows Figure 3 As shown in the combing work analysis of six test samples, 1kDa fermented silk protein peptide, 7kDa sodium hyaluronate and 11kDa sodium hyaluronate showed good film-forming and lubricating effects. The effects of 1kDa fermented silk protein peptide and 11kDa sodium hyaluronate were more prominent, and the improvement rate could reach more than 23%.
[0073] (3) Water retention performance test:
[0074] The experiment was carried out at a temperature of (25±2)°C and a RH of (50±5)%.
[0075] Take the hair bundle that has been pre-treated and bleached twice, wash it with 10% SDS in advance, and then place it in a constant temperature and humidity environment for 24 hours to dry naturally.
[0076] The hair bundles were soaked in deionized water and six groups of experimental sample aqueous solutions for 4 hours. After soaking, all the hair bundles were rinsed with warm water. After rinsing with warm water, the hair was combed ten times with similar force by hand, and then dried under constant temperature and humidity conditions.
[0077] The hair bundles of the control group and the treatment group were cut into small pieces with scissors, and the mass change under heating conditions was tested using a thermogravimetric analyzer. The test conditions were: heating to 65°C at a rate of 10°C / min and maintaining for 20 minutes, calculating the mass change before and after heating, and using this as the value of its free water content; then heating to 180°C at a rate of 10°C / min and maintaining for 20 minutes, calculating the mass change before and after heating, and using this as the value of its bound water content, and calculating the moisture content ratio of each group.
[0078] The results are shown in Table 1. Through the analysis of the water retention capacity of six test samples, 1kDa fermented silk protein peptide, 7kDa sodium hyaluronate, and 11kDa sodium hyaluronate showed good moisturizing effect, and the effects of 1kDa fermented silk protein peptide and 7kDa sodium hyaluronate were more prominent.
[0079] Table 1
[0080] Sample No. Free water ratio Bound water ratio Comparison 10.31% 1.97% Sample 1 11.45% 2.02% Sample 2 10.44% 1.97% Sample 3 10.65% 1.97% Sample 4 11.31% 2.01% Sample 5 11.02% 1.99% Sample 6 10.79% 1.98%
[0081] Example 3
[0082] In this example, the fermented silk protein peptide obtained in Example 1 was combined with hydrolyzed sodium hyaluronate in different proportions, and the combing performance and water retention performance of the different compound samples were tested.
[0083] (1) Preparation of experimental samples: Prepare samples according to Table 2, and make up the balance with deionized water; the control group is deionized water.
[0084] Table 2
[0085]
[0086]
[0087] (2) Combing performance test:
[0088] The sample processing method and experimental method are the same as in Example 2(2).
[0089] The results are as follows Figure 4 As shown, through the combing work analysis of six groups of test samples, the combination of 1% 1kDa fermented silk protein peptide, 0.4% 7kDa sodium hyaluronate and 0.6% 11kDa sodium hyaluronate showed good film-forming and lubricating effects, and the improvement rate could reach more than 35%.
[0090] (3) Water retention performance test:
[0091] The sample treatment method and experimental method are the same as those in Example 2 (3). The results are shown in Table 3. By analyzing the free water ratio and bound water ratio of the six groups of test samples, the combination of 1% 1 kDa fermented silk protein peptide, 0.4% 7 kDa sodium hyaluronate, and 0.6% 11 kDa sodium hyaluronate showed good water retention capacity.
[0092] Table 3
[0093] Sample No. Free water ratio Bound water ratio Comparison 10.35% 1.92% a 11.55% 2.03% b 11.71% 2.06% c 13.79% 2.15% d 11.98% 2.07% e 11.85% 2.04% f 12.03% 2.11%
[0094] Example 4
[0095] In this example, the fermented silk protein peptide obtained in Example 1 is compounded with a hydrolyzed sodium hyaluronate composition, and the combing performance and water retention performance of the compounded samples in different proportions are tested.
[0096] (1) Preparation of experimental samples: Prepare samples according to Table 4, and make up the balance with deionized water; the control group is deionized water.
[0097] Table 4
[0098] Sample No. 1kDa fermented silk protein peptide 7kDa:11kDa=4:6 Sodium hyaluronate A 2% 0% B 1.5% 0.5% C 1% 1% D 0.5% 1.5% E 0% 2%
[0099] (2) Combing performance test:
[0100] The sample processing method and experimental method are the same as in Example 2(2). Figure 5 As shown, through the combing work analysis of six groups of test samples, the compound combination of 1% 1kDa fermented silk protein peptide and 1% sodium hyaluronate (7kDa:11kDa=4:6) showed good film-forming and lubricating effects, and the improvement rate could reach more than 35%.
[0101] (3) Water retention performance test:
[0102] The sample treatment method and experimental method are the same as those in Example 2 (3). The results are shown in Table 5. By analyzing the free water ratio and bound water ratio of the six groups of test samples, the compound combination of 1% 1 kDa fermented silk protein peptide and 1% sodium hyaluronate (7 kDa: 11 kDa = 4: 6) showed good water retention capacity.
[0103] Table 5
[0104] Sample No. Free water ratio Bound water ratio Comparison 10.32% 1.96% A 11.34% 2.05% B 11.97% 2.08% C 13.72% 2.14% D 11.54% 2.01% E 11.57% 2.06%
[0105] Example 5
[0106] In this embodiment, fermented silk protein peptides and hydrolyzed sodium hyaluronate samples of different molecular weights are added to the product formula.
[0107] The product formula is shown in Table 6. Prepare the product solution according to the formula ratio in the table, and make up the balance with deionized water. The product solution needs to be fully stirred and mixed evenly.
[0108] Table 6
[0109] Raw material name Addition amount 400Da Hydrolyzed Collagen 10.00% 10kDa Hydrolyzed Keratin 1.00% 1kDa fermented silk protein peptide 1.00% 7kDa Sodium Hyaluronate 0.40% 11kDa Sodium Hyaluronate 0.60% Deionized water 87%
[0110] Example 6
[0111] In this example, the product solution in Example 5 was subjected to an anti-pollution test.
[0112] Healthy hair bundles were selected and stored at a constant temperature and humidity of (25±2)℃ and RH (50±5)%. The hair bundles were smeared with 0.3g of the product and then dried under constant temperature and humidity conditions. The control group was an untreated hair bundle. After simulating a polluted environment in a pollution simulation box for 12 hours, the hair bundles were placed in a constant temperature and humidity environment for 24 hours before SEM testing.
[0113] Figure 6 It can be seen that the dust deposition on the hair surface of the control group is obvious and the deposition amount is large, while the hair surface treated with the product solution has almost no dust deposition. Therefore, it can be seen that the product solution has a significant effect in resisting dust deposition, which can reduce the impact of environmental pollution on the mechanical properties of hair, thereby reducing hair breakage.
[0114] Example 7
[0115] In this example, the product solution in Example 5 was subjected to a permeability test.
[0116] Dissolve TAMRA-SE in DMF to prepare a 10 mg / mL solution as the dyeing mother solution, and store it away from light for later use. Add disodium hydrogen phosphate and sodium dihydrogen phosphate to the product sample to prepare it into a pH = 7 buffer system. Take the treated raw material solution and mix it with an equal volume of the dye mother solution, shake it gently on a shaker overnight (about 12 hours), take the supernatant after centrifugation and dialyze it for 12 hours to fully remove the organic solvent DMF. Due to solubility limitations, the dye molecules that have not reacted with the raw material will precipitate from the solution, and the fluorescent dye will remain in the solution after combining with the dye;
[0117] Take a bunch of pretreated natural white hair, soak it in the dyed product sample solution for 4 hours, take it out and rinse it repeatedly with deionized water for 30 seconds, and dry it under constant temperature and humidity conditions. After drying, treat it with an embedding agent, slice it with a microtome, and then observe the hair with a fluorescence microscope.
[0118] The results are as follows Figure 7 As shown, it shows that the labeled high and low molecular weight fermented silk protein peptides and hydrolyzed sodium hyaluronate can evenly penetrate into all parts of the hair.
[0119] Example 8
[0120] In this example, the surface properties of the product solution in Example 5 were tested.
[0121] (1) Detection of friction coefficient
[0122] The experiment was conducted at a temperature of (25±2)°C and a relative humidity of (50±5)%. The hair strands that had been pre-treated and bleached twice were washed with 10% SDS and then placed in a constant temperature and humidity environment for 24 hours to dry naturally.
[0123] Two hair bundles that had been pre-treated and bleached twice were selected, one of which was soaked in the product solution in Example 5 for 4 hours, and the other was soaked in deionized water as a control group. Both hair bundles were rinsed with warm water after soaking, and then brushed ten times with similar force by hand, and then dried under constant temperature and humidity conditions.
[0124] After being stored under constant temperature and humidity conditions for 12 hours, 15 hair bundles were randomly selected and the fiber friction coefficient was tested in a fiber friction coefficient tester.
[0125] The test results are in Figure 8 It is shown in the figure that the dynamic friction coefficient is significantly reduced after treatment with the product solution, showing a good lubrication effect.
[0126] (2) Combing performance test
[0127] The sample processing method and experimental method are the same as in Example 2(2). Fig. 9 As shown, the product solution exhibits good film-forming and lubricating properties, and the improvement rate can reach more than 47%.
[0128] In summary, in terms of the macro-combability of hair bundles and the micro-friction of hair, the product solution has a significant instant smoothing effect, which can reduce the phenomenon of hair breakage due to friction in daily life.
[0129] Example 9
[0130] In this example, the water retention performance of the product solution in Example 5 was tested.
[0131] The sample treatment method and experimental method are the same as those in Example 2 (3). As shown in Table 7, the percentages of free water and bound water after treatment with the product solution increased, indicating that the product solution has good moisturizing properties.
[0132] Table 7
[0133] Sample No. Free water ratio Bound water ratio Control group 10.45% 1.92% Treatment Group 14.54% 2.25%
[0134] Example 10
[0135] In this example, the tensile properties of the product solution in Example 5 were tested.
[0136] The experiment was conducted at a temperature of (25±2)°C and a relative humidity of (50±5)%. The hair strands that had been pre-treated and bleached twice were washed with 10% SDS and then placed in a constant temperature and humidity environment for 24 hours to dry naturally.
[0137] Two pre-treated, twice bleached hair bundles were selected, one of which was soaked in the product solution for 4 hours, and the other was soaked in deionized water as a control group; both soaked hair bundles were rinsed with warm water, and after rinsing with warm water, the hair was combed ten times with similar force by hand, and then dried under constant temperature and humidity conditions.
[0138] Two bundles of hair were used for strength test, and the ability of the product solution to strengthen hair was evaluated by calculating the tensile strength and yield zone tension. The specific test and calculation methods are as follows:
[0139] The diameter of the repaired hair samples was measured using an SN-1200W high-definition camera. Thirty hairs with a diameter difference of less than 15 μm (75-90 μm) were taken from two bundles of hair and tested for single fiber strength using a fiber strength tester. The tensile strength of the hair fibers was calculated using the following formula:
[0140] σ=Fb / S 0
[0141] Where σ is the tensile strength, F b is the maximum force that the hair bears when it is broken, S 0 is the cross-sectional area of the hair. The tensile force in the yield zone of the hair is calculated by the following formula:
[0142] F Y =(F h +F y ) / (2×S 0 )
[0143] Where F Y is the yield zone tension, F h is the tension at the end of the Hooke's zone, F y is the tension at the end of the yield zone, S 0 is the cross-sectional area of the hair.
[0144] The results are as follows Fig.10 , 11 As shown, the product solution significantly improves both the breaking strength and the tensile strength in the yield zone of the hair, indicating that the product solution can achieve the toughening and tensile resistance effects of the hair.
[0145] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A composition of fermented silk protein peptide and hydrolyzed sodium hyaluronate, characterized in that: include, 1kDa fermented silk protein peptide, 1-10kDa sodium hyaluronate, 10-50kDa sodium hyaluronate and deionized water; Among them, based on the mass percentage of each raw material, the molecular weight of 1kDa fermented silk protein peptide is 0.5-20%, the molecular weight of 1-10kDa sodium hyaluronate is 0.1-10%, the 10-50kDa sodium hyaluronate is 0.1-10%, and the rest is made up to 100% with deionized water.
2. The composition according to claim 1, characterized in that: The molecular weight of the sodium hyaluronate with a molecular weight of 1-10 kDa is 7 kDa.
3. The composition according to claim 1 or 2, characterized in that: The molecular weight of the sodium hyaluronate with a molecular weight of 10-50 kDa is 11 kDa.
4. The composition according to claim 3, characterized in that: The content of the fermented silk protein peptide with a molecular weight of 1 kDa is 1%, the content of the sodium hyaluronate with a molecular weight of 7 kDa is 0.4%, the content of the sodium hyaluronate with a molecular weight of 11 kDa is 0.6%, and the rest is supplemented with deionized water to 100%.
5. The composition according to claim 4, characterized in that: The method for preparing the fermented silk protein peptide with a molecular weight of 1 kDa comprises: Silk protein powder was dissolved in deionized water, pasteurized, and cooled to obtain solution A; Dissolve anhydrous glucose in deionized water, sterilize by high pressure, and cool to obtain solution B; Mixing solution A and solution B evenly under sterile conditions to prepare a fermentation medium; The plant lactobacillus was cultured in MRS medium until OD600nm=7-8, then inoculated into the fermentation medium at a volume fraction of 2%-5%, and cultured in a 37°C constant temperature incubator for 24-48 hours, and the fermentation was terminated when the residual sugar reached 0; After the fermentation is completed, the fermentation liquid is filtered through a 0.2 μm microfiltration membrane, and the filtrate is a fermented silk protein peptide solution with a molecular weight of 1 kDa.
6. The composition according to claim 5, characterized in that: The plant lactobacillus is Lactobacillus plantarum (Lactobacilus plantarum) ZW, which is preserved in the China Center for Type Culture Collection, with a preservation number of CCTCC NO: M20232390 and a preservation date of November 29, 2023.
7. A method for preparing a composition according to any one of claims 1 to 6, characterized in that: The method comprises the steps of uniformly mixing fermented silk protein peptide with a molecular weight of 1 kDa, sodium hyaluronate with a molecular weight of 1 to 10 kDa, sodium hyaluronate with a molecular weight of 10 to 50 kDa and deionized water to prepare the composition.
8. Use of the composition according to any one of claims 1 to 6 in the preparation of hair care products.
9. The use according to claim 8, characterized in that: include, Prepare raw materials: 400Da hydrolyzed collagen, 10kDa hydrolyzed keratin, and the composition; Mixing evenly: mixing 400Da hydrolyzed collagen, 10kDa hydrolyzed keratin and the composition evenly to prepare the hair care product.
Citation Information
Patent Citations
Preparation method and application of madecassic diglucoside fermentation product
CN117821520A
Lactic acid bacteria with skin cell repairing capability and application of lactic acid bacteria in cosmetics
CN118028139A